Understanding the Somalia conflagration identity, political Islam and peacebuilding - Elmi, Afyare Abdi (Pluto Press, 2010)
Somalia has been devastated by a US-backed Ethiopian invasion and years of civil war, and it has long been without a central government. Against this background of violence, Somali academic Afyare Abdi Elmi, attempts to explain the multiple dimensions of the conflict and find a peace-building consensus. Somalia is a failed state and a Muslim state. This combination means the West assumes that it will become a breeding ground for extremism. The country regularly hits the headlines as a piracy hotspot. This combination of internal division and outside interference makes for an intensely hostile landscape. Elmi shows that only by addressing the problem of the statelessness in the country can the long process of peace begin. He highlights the various factors involved, including clan identities, Islam and other countries in the region, as the key elements in any peace-building effort. This is a unique account from an author who truly understands Somalia and should be required reading for students and academics of international relations and peace / conflict studies. -- Publisher description.